Buckling of a column with rigid segments on an elastic foundation. (June 2020) - Wang, C.Y.
Abstract: A beam-column consisting of linked rigid segments with rotational resistance at the joints rests on an elastic foundation. The buckling problem due to axial compression is formulated for N identical segments. The characteristic equation show the buckling force depends on N and a parameter representing the relative importance of joint rigidity and foundation resistance. Exact solutions are found for columns up to N = 5 segments.